2021
DOI: 10.1177/03000605211037475
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral radiculopathy after unilateral transforaminal lumbar interbody fusion: causes and prevention

Abstract: Background Unilateral transforminal lumbar interbody fusion (TLIF) with a single cage can provide circumferential fusion and biomechanical stability. However, the causes and prevention of contralateral radiculopathy following unilateral TLIF remain unclear. Methods In total, 190 patients who underwent unilateral TLIF from January 2017 to January 2019 were retrospectively reviewed. Radiological parameters including lumbar lordosis, segmental angle, anterior disc height, posterior disc height (PDH), foraminal he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Unilateral TLIF has also been shown to cause a contralateral radiculopathy with an incidence of up to 5.3%. 11 This was attributed to undiagnosed contralateral foraminal stenosis, improper noncentral asymmetric cage placements, undersized cages, excessive compression to create lumbar lordosis and a Nondecompression newly herniated disc due to insufficient disc removal and the use of unilateral cages pushing the disc material to the contralateral side. [12][13][14][15] Some authors have even recommended for prophylactic decompression of the contralateral side in open cases where foraminal stenosis cannot be visualized without prior decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral TLIF has also been shown to cause a contralateral radiculopathy with an incidence of up to 5.3%. 11 This was attributed to undiagnosed contralateral foraminal stenosis, improper noncentral asymmetric cage placements, undersized cages, excessive compression to create lumbar lordosis and a Nondecompression newly herniated disc due to insufficient disc removal and the use of unilateral cages pushing the disc material to the contralateral side. [12][13][14][15] Some authors have even recommended for prophylactic decompression of the contralateral side in open cases where foraminal stenosis cannot be visualized without prior decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Incorrect diagnosis and surgical indication translate into complications and technical difficulties, which, in some cases, can cause radiculopathy ipsilateral or contralateral to the approach, this secondary to a sagittal and coronal imbalance due to the lateral and posterior positioning of the intersomatic box even in the 5% of cases. 25 Cage subsidence is associated with elevated BMI (body mass index), paravertebral muscle injury, implant characteristics such as size greater than 12 mm, titanium-coated PEEK (Poly-ether-ether-ketone) and a combination of grafts types. 26 In addition, the use of postoperative spinal orthosis to prevent complications of instability and increase the percentage of fusion is not indicated, since it has been discovered that it does not influence superiority to non-use, but it does increase muscle atrophy, which, in certain patients, can be counterproductive.…”
Section: Complicationsmentioning
confidence: 99%
“…However, it is not without complications, and contralateral root symptoms after unilateral TLIF are a common complication that may affect the overall efficacy of the surgery [3,4]. Previous studies by domestic and international scholars have identified preoperative contralateral intervertebral foramen stenosis, large lumbar sagittal plane mobility, and intraoperative fusion device position to one side as important risk factors for the development of contralateral root symptoms after unilateral TLIF [5,6]. However, these studies have several limitations, including a lack of quantification of research results and limited clinical significance.…”
Section: Introductionmentioning
confidence: 99%